Tryptophan Metabolism through the Kynurenine Pathway is Associated with Endoscopic Inflammation in Ulcerative Colitis. Issue 7 (22nd May 2018) - Sofia, M Anthony; Ciorba, Matthew A; Meckel, Katherine; Lim, Chai K; Guillemin, Gilles J; Weber, Christopher R; Bissonnette, Marc; Pekow, Joel R
Abstract: Background and Aims: Mucosal appearance on endoscopy is an important indicator of inflammatory burden and determines prognosis in ulcerative colitis (UC). Inflammation induces tryptophan metabolism along the kynurenine pathway (KP) and yields immunologically relevant metabolites. We sought to examine whether changes in serum tryptophan metabolites and tissue expression of KP enzymes are associated with UC endoscopic and histologic disease severity. Methods: Serum and mucosal samples were prospectively obtained at colonoscopy in patients with UC. Mayo disease activity scores, demographics, smoking status, medications, and outcomes were collected. Serum tryptophan metabolites were analyzed using ultra-high performance liquid chromatography (uHPLC), and gas chromatography-mass spectrometry (GC-MS), and enzyme expression was determined by quantitative real-time polymerase chain reaction. Metabolite and enzyme levels were compared by endoscopic subscore, clinical disease activity, time to surgery, and hospitalization. Results: This study included 99 patients with Mayo endoscopic subscores 0–3. Kynurenic acid/tryptophan ratio (KYNA/T) and expression of indolamine 2, 3-dioxygenase 1 (IDO1), tryptophan 2, 3-dioxygenase, kynurinase, and kynurenine monooxygenase correlated positively with endoscopic subscore. Adjusting for age of diagnosis, smoking status, disease extent, and medications yielded significant odds of endoscopic inflammation with increasing KYNA/T (OR 1.0015, P = 0.0186) and IDO1 expression (OR 1.0635, P = 0.0215). The highest tertile ratio of KYNA/T had shorter time to surgery ( P = 0.009) and hospitalization ( P = 0.01) than the lowest. Conclusions: Increasing KYNA/T is closely associated with endoscopic inflammation and predictive of disease outcomes in patients with UC. These findings identify this novel metabolic association and further support the role of the KP in regulating mucosal inflammation in UC.